Formas híbridas: o lirismo em Ressurreição e Dom Casmurro de Machado de Assis - Prado, Kelly Beatriz do (2010)
The objective of this dissertation is to contemplate on hybrid forms in the romances Ressureição and Dom Casmurro of Machado of Assis, with the intention of apprehending a lyrical slope in the romantic prose of his. To reach this aim, the following subject-problem guided us: How is the hybrid character configured in these romances? Has the conjunction of the lyrical with the narrative build in Dom Casmurro already find delineated in Ressureição? The theory base of this research is based in Questões de Literatura e de Estética: the theory of Mikhail Bakhtin's romance (1998), that treats of the aesthetic bases of the romance while gender and of its capacity to embrace other speech forms, just as the speech of lyrical modulation. The conception of lyrical romance leans on in the studies of Rosa Maria Goulart, entitled: Romance Lírico: Vergílio Ferreira's course (1990) and O trabalho da Prosa: Narratives, Rehearsals, Epistemography (1997). As conclusion, in Ressureição, the presence of the third-person narrator is responsible for the restriction of the lyricism to the micro structures and in Dom Casmurro, the presence of the first-person narrator opportune the lyrical expansion for whole the speech, characterizing the romance as lyrical. The lyrical slope apprehended in the two romances is configured because of: the hybrid, the registration, the subjectivity, the emotional intensification, the tension and darkness of the statements, having the negative and the irony as forms of contention of the sentimentalism